2022
DOI: 10.2337/ds21-0056
|View full text |Cite
|
Sign up to set email alerts
|

Association of Type 2 Diabetes Risk Perception With Interest in Diabetes Prevention Strategies Among Women With a History of Gestational Diabetes

Abstract: Objectives The aims of this study were to identify predictors of perception of type 2 diabetes risk in women with a history of gestational diabetes mellitus (GDM) and to determine factors associated with interest in evidence-based strategies for type 2 diabetes prevention. Research Design and Methods We surveyed women with a history of GDM who had not progressed to type 2 diabetes from a large academic medical center. We used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These findings are concerning as greater risk perception among women has been associated with engagement in a formal postpartum lifestyle-change program [31]. Combined, these studies underscore the importance of healthcare providers effectively conveying long-term health risks associated with reproductive-aged women's personal health profiles.…”
Section: Delayed Resultsmentioning
confidence: 99%
“…These findings are concerning as greater risk perception among women has been associated with engagement in a formal postpartum lifestyle-change program [31]. Combined, these studies underscore the importance of healthcare providers effectively conveying long-term health risks associated with reproductive-aged women's personal health profiles.…”
Section: Delayed Resultsmentioning
confidence: 99%
“…A randomized controlled trial conducted among individuals with family history of diabetes found that 34.6% of those in the intervention group and 40.6% of those in the control group perceived their risk of diabetes to be likely or very likely [ 35 ]. Studies found that 20% [ 20 ], 45% [ 25 ], 60.8% [ 28 ] and 72% [ 26 ] of women who were currently or previously diagnosed with gestational diabetes mellitus perceived high risk of type 2 diabetes. Other studies presented the scores of diabetes risk perception using mean and standard deviation without classifying the scores [ 19 , 21 , 23 , 24 , 29 , 30 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…These ndings are concerning as greater risk perception among women has been associated with engagement in a formal postpartum lifestyle-change program. 29 Combined, these studies underscore the importance of healthcare providers effectively conveying long-term health risks associated with reproductive-aged women's personal health pro les. In a report by Wilkinson et al, an Australian-based qualitative study with postpartum women who had had GDM or overweight/obesity, women said they desired a tailored and supportive lifestyle program offered by trusted professionals and women with lived experience that would account for the "new normal" of motherhood while also providing methods of accountability.…”
Section: Discussionmentioning
confidence: 99%